Analysis and Synthesis of Outside Geneva Combined Mechanism with Uniform Movement - Zhou Hongying; Han Jiguang (Jixie chuandong)
The kinematic characteristics of the ordinary geneva wheel mechanism are determined by the numbers of sheave groove. The drive crank of geneva wheel is the cycloid production mechanism which equals to the mechanism with a variable length,variable speed and along the cycloid moving crank and makes the kinematic characteristic of the geneva mechanism changed. The forming condition of the outside geneva mechanism with uniform movement are analyzed,then on this basis the design method and the mechanism parameters are proposed. The change rule of the uniform movement interval and the influence of movement coefficient on the width of approximate uniform movement interval and the fluctuation quantity of angular velocity in approximate uniform movement interval are analyzed,the calculation method of the width and the fluctuation quantity of angular velocity of the uniform movement interval are given.